2011
DOI: 10.1111/j.1365-2656.2011.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

The indirect consequences of a mutualism: comparing positive and negative components of the net interaction between honeydew‐tending ants and host plants

Abstract: Summary1. In ecological webs, net indirect interactions between species are composed of interactions that vary in sign and magnitude. Most studies have focused on negative component interactions (e.g. predation, herbivory) without considering the relative importance of positive interactions (e.g. mutualism, facilitation) for determining net indirect effects. 2. In plant ⁄ arthropod communities, ants have multiple top-down effects via mutualisms with honeydew-producing herbivores and harassment of and predation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 30 publications
2
48
0
1
Order By: Relevance
“…In a previous study, ants had a negative net effect on plants due to the ant–treehopper mutualism and the treehopper's effect on plants (red paths) (Grinath et al . ). Interactions between non‐ant arthropod predators and herbivores are shown in grey to highlight paths that may be altered by intraguild predation.…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, ants had a negative net effect on plants due to the ant–treehopper mutualism and the treehopper's effect on plants (red paths) (Grinath et al . ). Interactions between non‐ant arthropod predators and herbivores are shown in grey to highlight paths that may be altered by intraguild predation.…”
Section: Introductionmentioning
confidence: 97%
“…Although the above scenario may arise from the three trophic level interaction mentioned above, it has been suggested that ants may also repel chewing insects by consuming honeydew, decreasing their abundance and activity on plants [133]. The different responses of herbivores to abundance of ants found in our study suggest that the effect of ants on herbivores is dependent of herbivore feeding habits.…”
Section: Biodiversity and Ecosystem Functioning In Tropical Habitats mentioning
confidence: 35%
“…The different responses of herbivores to abundance of ants found in our study suggest that the effect of ants on herbivores is dependent of herbivore feeding habits. Several studies have reported non-obligatory interactions between ants and sap-sucking insects [123,[130][131][132][133][134]. In this interaction, ants feed on the honeydew and protect the insects against predators and competitors [130].…”
Section: Biodiversity and Ecosystem Functioning In Tropical Habitats mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of community ecology, focused on negative interactions between species, has led to the neglect of positive interactions and its importance in food webs (Ohgushi, 2008;Grinath et al, 2012). The effect of Hemiptera-ant interaction can cause changes in community in terms of abun- dance, distribution and survival of the associated arthropods (Del-Claro & Oliveira, 2000;Renault et al, 2005;Styrsky & Eubanks, 2006).…”
Section: Discussionmentioning
confidence: 99%